Knowledge, attitude, and practice of cervical cancer screening among women living with HIV in the Kilimanjaro region, northern Tanzania. Issue 5 (19th March 2021) - Kimondo, Faustini C.; Kajoka, Happiness D.; Mwantake, Meshack R.; Amour, Caroline; Mboya, Innocent B.
Abstract: Background: Cervical cancer is the fourth most common cancer globally among women in incidence and mortality. Women living with HIV (WLHIV) are disproportionately at a higher risk of developing the disease. Aim: To determine the knowledge, attitude, and practice of cervical cancer screening among WLHIV in the Kilimanjaro region, northern Tanzania, following the integration of these services in routine HIV care in the country. Methods and results: A cross‐sectional study was conducted in the Kilimanjaro region among 297 WLHIV attending care and treatment centers (CTC) in Hai district and Mawenzi regional hospitals in northern Tanzania between 21 August and 3 September 2020. A questionnaire was used for data collection using face‐to‐face interviews. Data were analyzed using SPSS version 20.0. Frequencies and percentages summarized categorical variables and numerical variables summarized using median and interquartile range (IQR). About half (50.2%) of 297 WLHIV in this study had ever screened for cervical cancer, and 64% screened within the past 12 months preceding the survey. Although 90% ever heard of cervical cancer screening, only 20.5% knew when WLHIV should start screening. Over half (52.5%) had adequate knowledge of prevention, 38.4% on risk factors, and 27.9% of cervical cancer signs and symptoms. Two‐thirds (66.7%) had positive attitudes toward cervical cancer screening. A major source of cervical cancer screening information was the health care providers (80.1%) and the mass media (66%), particularly radio. Conclusions: The WLHIV in this study had inadequate knowledge but favorable attitudes toward cervical cancer screening, while half had screened for cervical cancer. Efforts should be directed to capacity building of health care providers at CTC and scaling up the mass media campaigns as relevant interventions to promote the uptake of cervical cancer screening programs among WLHIV in Tanzania.